Optimization of HFMI/PIT Parameters with Simultaneous Multiple Response Consideration using Multi-Objective Taguchi Method for Fatigue Life Enhancement of Friction Stir Welding - Mohamed, Mohamed Ackiel; Manurung, Yupiter HP; L. H., Shah; Nurul Hidayah, Othman (2015)
The friction stir welding process is witnessing a growth in its application in a wide range of The friction stir welding (FSW) process is witnessing a growth in a wide range of industrial applications due the minimal governing parameters and many other advantages as a solid state welding compared to the commonly used fusion welding process. However, tensile residual stress remains to be significant concern due to its extensive clamping and stirring process which can lead to lower fatigue resistance particularly in structures subjected to fluctuating loads. Up to day, research dealing with fatigue enhancements methods for FSW is rarely found in literature. This novel study presents an unconventional method to optimize the governing process parameters of Pneumatic Impact Treatment (PIT) also known as one of the High Frequency Mechanical Impact (HFMI) techniques. The post weld treatment is aimed to enhance fatigue resistance of FSW butt joints. The experimental study was conducted for Aluminum alloy (AA 6061) plates with thickness of 6 mm under varied PIT parameters centered on the intender pin diameter, applied air pressure and hammering frequency. The investigation began with obtaining optimum parameters for single response by using conventional Taguchi method with L9 orthogonal array. Further, advanced optimization approach by means of Multi-objective Taguchi Method (MTM) attempts to consider the multiple quality features simultaneously which are hardness value and fatigue life cycle. The significant level of the PIT parameters was investigated by using analysis of variance (ANOVA). As the final results, the optimum value was acquired by calculating the total normalized quality loss (TNQL) and multi signal to noise ratio (MSNR). Subsequent confirmation test was conducted upon determination of the optimized PIT parameters.